Prospective Science Teachers' Self-efficacy Beliefs about Teaching Science between 6-8 Terms and the Opinions on These Beliefs - (:unkn) unknown (EDAM, 2013)
The formal educational institutions and the society have an important function in acquiring a sense of self-efficacy. Teachers play a role in the formal educational process. The purpose of the study is to examine prospective science teachers' self-efficacy belief level in the 6th to 8th terms and the differences in this process. This survey model study was applied in the spring semester of 2009-2010, the fall and spring semesters of the academic year 2010-2011. 40 prospective science teachers, from Marmara University Primary Science Education Department, participated in the study for three semesters. The data was collected by science teaching self-efficacy belief scale, interview questions and video recordings. The data of the scale was analyzed with paired sampled t-test and the descriptive statistical technique. Interview questions were analyzed by open-coding, and the results were interpreted in tables. According to the findings, participants' self-efficacious for science teaching is usually good; and it is determined from this context they found themselves quite efficient to teach science. Besides, prospective science teachers have a positive attitude towards the lessons which offer opportunity to practice. The practical lessons are highly significant for the prospective science teachers' self-efficacy beliefs.
Keywords: Science Education Self-efficacy Belief; Personal Self-efficacy in Science Teaching; Result Expectation in Science Teaching; Prospective Teacher; Science Education; CONSTRUCT